Characteristics Study of Land for Agriculture in Sembalun - Irradhiyah, Azmi Annisa (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research aims to get the data, manage, analyze and discuss the characteristics of the study of Agricultural Land in Sembalun visits: 1 ) Characteristics of agricultural land, 2) Level of agricultural land suitability. This type of research is quantitative. This study population across the districts in East Lombok, amounting to 20 District of the District Keruak, Jerowaru, Sakra, Sakra West, Sakra East, Terara, Montong Ivory, Sikur, Masbagik, Pringgasela, Sukamulia, Suralaga, Selong, Labuhan Haji, Pringgabaya , Suela, Aikmel, Wanasaba Sembalun and Sambelia. Sampling in this study using Purvosive Sampling. Samples are Sembalun subdistrict. Mechanical Analysis by objective research of agricultural land characteristics observed descriptively and databulasi of the field data belongs to the growing requirements of agriculture which can be seen from the slope, soil structure, slope length, slope shape, texture soil, land use criteria. The research found that: 1) Characteristics of agricultural land in Sembalun, had several criteria: a slope in the category Sembalun including steep or less suitable for agriculture by 46-65% kemiringin slope, soil to soil Sembalun criteria granular, blocky or appropriate agricultural land and have long used the medium to long 15-50m, soil texture Sembalun criteria belong to the category of rough because it is composed by sand-plated, dusty sand, slope shape in Sembalun belong to the variation convex with dignity 2 for observation location along notching it is always a convex slope, land use Sembalun belong to the criterion of berlukar / mixed farms with dignity 2. Because along the way, the land berlukar / mixed farms. 2) Suitability of farmland in Sembalun based on the results of pengharkatan to 6 land characteristics, the number value obtained was 12 with class suitability for agricultural land belonging to the class I (land suitable for agriculture).